Cardiovascular and Metabolic Crosstalk in the Brain: Leptin and Resistin - Badoer, Emilio (Frontiers in Physiology, 2021)
Leptin and resistin are cytokines whose plasma levels correlate with adiposity. Leptin is a hormone synthesised and released from adipocytes and can be transported into the brain. Resistin is produced in adipocytes in rodents and in macrophages in humans, particularly macrophages that have infiltrated adipose tissue. Both hormones can act within the brain to influence sympathetic nerve activity. Leptin appears to have a generalised sympatho-excitatory actions whilst resistin appears to increase sympathetic nerve activity affecting the cardiovascular system but inhibits sympathetic nerve activity to brown adipose tissue, which contrasts with leptin. Since both hormones can be elevated in conditions of metabolic dysfunction, interactions/crosstalk between these two hormones in the brain is a real possibility. This review describes the current knowledge regarding such crosstalk within the central nervous system. The evidence suggests that with respect to sympathetic nerve activity, crosstalk between leptin and resistin can elicit enhanced sympatho-excitatory responses to the kidneys. In contrast, with respect to food intake, resistin has weaker effects, but in regard to insulin secretion and thermogenesis, leptin and resistin have opposing actions. Thus, in conditions in which there is increased resistin and leptin levels, the result of crosstalk in the central nervous system could contribute to worse cardiovascular and metabolic complications.